Educaplay como herramienta tecnológica en el proceso de enseñanza–aprendizaje, para los docentes del (centro educativo comunitario intercultural bilingüe) cecib “República del Ecuador” de la ciudad de Guaranda, provincia Bolívar, periodo lectivo 2023 – 2024 - Manobanda Chaquinga, Bryan Alexander (2024)
This work is oriented to the use of Educaplay as a technological tool in the teaching- learning process for teachers of the CECIB “República del Ecuador” (Intercultural Bilingual Community Education Center) in the city of Guaranda, Bolivar Province, school year 2023 - 2024. The objective is to strengthen the technological and pedagogical support through Educaplay in the academic process for teachers in the CECIB “República del Ecuador”, a manual was designed to implement it in the development of educational activities of the institution. The methodology describes the resources and procedures used in the research; the materials used are a survey, interview, each one with their respective instruments; as a method the quantitative and qualitative approaches were used that allowed the description, analysis and interpretation of the results obtained, as a study design the bibliographic, descriptive and field methods were used, the population sample was composed of 10 teachers and 15 students. A theoretical framework was developed, with a bibliographic research based on books, magazines and internet, which allowed obtaining true and necessary information contributing to a bibliographic support. As a conclusion, it became evident that the use and execution of activities through Educaplay is characterized because it promotes interaction and participation between teacher- student. This tool facilitates the development of competencies through the implementation of gamification, both for the activities carried out by the teacher or through its extensive repository. Finally, a user's manual for teachers was developed.